The analysis of extreme tropopause fold events at Syowa Station in the Antarctic - Mizukoshi, Masatoshi; Kohma, Masashi; Sato, Kaoru (2020)
The 11th Symposium on Polar Science/Interdisciplinary sessions: [IW] Whole atmosphere, Thu. 3 Dec. conference object